Non-ideal magnetohydrodynamics on a moving mesh - Marinacci, Federico; Vogelsberger, Mark; Kannan, Rahul; Mocz, Philip; Pakmor, Rüdiger; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. In certain astrophysical systems, the commonly employed ideal magnetohydrodynamics (MHD) approximation breaks down. Here, we introduce novel explicit
Gesehen am 08.02.2019